Chemical insights into the formation of Cu2ZnSnS4 films from all-aqueous dispersions for low-cost solar cells. (10th October 2017) - Foncrose, Vincent; Persello, Jacques; Puech, Pascal; Chane-Ching, Jean Yves; Lagarde, Delphine; Balocchi, Andrea; Marie, Xavier
Abstract: Cu2 ZnSnS4 (CZTS) shows great potential for photovoltaic application because of its non-toxic earth-abundant components and good optoelectronic properties. Combining low-cost and environmentally friendly routes would be the most favorable approach for the development of CZTS solar cells. In this context, development of Cu2 ZnSnS4 (CZTS) films from all-aqueous CZTS nanocrystals inks represents an interesting challenge. Here, we have highlighted a condensation regulation by the alkali ion size observed in the alkali series Li +  < Na +  < K +  < Rb +  < Cs +, and demonstrated the chemical stability of Cu2 ZnSnS4 surfaces in basic aqueous dispersions. Data such as optimal nanocrystal size, critical cracking thickness and average thickness to fabricate micron crack-free films from all-aqueous chalcogenide nanocrystals dispersions were determined. From these results, a proof of concept for the formation of a crack-free film of 2.2 μ m formed from an all-aqueous CZTS nanocrystals ink is given. When employing low-cost materials, removal of carbon impurities represents another important challenge. With the objective to fabricate residue-free films, a specific annealing strategy is proposed involving a high temperature purification step under Se partial pressure. Carbon removal is thus achieved via the CSe2 gas formation, simultaneously to the amorphous domains crystallization as demonstrated by Raman spectroscopy. These source data favoring the formation of residue-free, crack-free, annealed films should assist the large scale development of CZTS solar cells from low-cost and environmentally friendly, all –aqueous inks.